If $x[n]=(0.5)^nu[n]$ and $y[n]=(x*x)[n]$ then what is the value of $\sum\limits_{n=-\infty}^{\infty}y[n]$ ?

I calculated the $\mathcal{Z}$-transform of $x[n]$ and then applied the accumulation property of $\mathcal{Z}$-transform. $$X(z) = \frac{1}{1-0.5z^{-1}}\\ Y(z) = \bigg(\frac{1}{1-0.5z^{-1}}\bigg)^2\\ \sum\limits_{n=-\infty}^{\infty}y[n] \longleftrightarrow \bigg(\frac{1}{1-0.5z^{-1}}\bigg)^2.\bigg(\frac{1}{1-z^{-1}}\bigg)$$ Please point out the mistake I am doing. Thanks in advance for the help.

  • $\begingroup$ What does your $*$ symbol mean? Convolution or multiplication ? $\endgroup$
    – Hilmar
    Oct 9 at 15:54
  • 2
    $\begingroup$ Interestingly enough the answer is the same for both multiplication or convolution, but it's a different path to get there. Your third equation is nonsense. Keep it mind that the sum is simply the z-transform at $ z = 1$ $\endgroup$
    – Hilmar
    Oct 9 at 16:03
  • $\begingroup$ @Hilmar the $\textbf{*}$ symbol is convolution. Can you please explain a little bit? Isn't the third equation valid for sums? $\endgroup$
    – edison
    Oct 9 at 16:15

I was following you but I'm not sure where your last equation comes from. You want to use $Y(z)$ as I describe below.

This is the kind of problem that makes sense only if you "see it" in my opinion. The trick is that $\sum_{n=-\infty}^{\infty}y[n]$ can be computed by evaluating the z-transform at $z=1$. Remember that the z-transform equation is:

$$ Y(z)=\sum_{n=-\infty}^{\infty}y[n]z^{-n} $$

and so if we set $z=1$, we arrive at:

$$ Y(0)=\sum_{n=-\infty}^{\infty}y[n]$$


Let's say we have a signal and it's z transform

$$x[n] \longleftrightarrow X(z)$$

and the convolution with itself

$$y[n] = (x*x)[n] \longleftrightarrow Y(z)$$

Convolution in the time domain is multiplication in the frequency domain, so we have

$$Y(z) = X^2(z)$$

The sum over each sequence is

$$\sum_{-\infty}^{\infty}x[n] = X(z)_{z=1}$$

Hence we have $$\sum_{-\infty}^{\infty}y[n] = Y(z)_{z=1} = X(z)^2_{z=1}$$

In the time domain this looks like.

$$\sum_{-\infty}^{\infty}y[n] = (\sum_{-\infty}^{\infty}x[n])^2$$

The simple answer: figure out the sum over $x[n]$ and square it. Hint: $2\cdot 2 = 4$.

  • $\begingroup$ +1 Oh, shoot! I was always taught that it is $2+2$ that equals $4$, so presumably in this case, addition is the same as multiplication which is the same (cf. your comment on the OP's question) as convolution :-) $\endgroup$ Oct 10 at 20:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.